2017
DOI: 10.1136/bmjopen-2016-013342
|View full text |Cite
|
Sign up to set email alerts
|

Precision orthotics: optimising ankle foot orthoses to improve gait in patients with neuromuscular diseases; protocol of the PROOF-AFO study, a prospective intervention study

Abstract: IntroductionIn patients with neuromuscular disorders and subsequent calf muscle weakness, metabolic walking energy cost (EC) is nearly always increased, which may restrict walking activity in daily life. To reduce walking EC, a spring-like ankle-foot-orthosis (AFO) can be prescribed. However, the reduction in EC that can be obtained from these AFOs is stiffness dependent, and it is unknown which AFO stiffness would optimally support calf muscle weakness. The PROOF-AFO study aims to determine the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…The reported control of the mechanical properties of an AFO, such as bending stiffness, damping stiffness, and assistive torque, showed both fixed and adaptive output references. It could be clearly observed that the fixed output reference worked with a flexible rigid AFO [18,64] and an AFO with only mechanical actuators, such as an oil damper [69] and a spring [32,73]. The adaptive output reference could be observed from those works that utilized electrical actuators such as an MR device [41,49,56], SEA [54,75], and a pneumatic system [53].…”
Section: Output Reference: Fixed Versus Adaptivementioning
confidence: 99%
See 2 more Smart Citations
“…The reported control of the mechanical properties of an AFO, such as bending stiffness, damping stiffness, and assistive torque, showed both fixed and adaptive output references. It could be clearly observed that the fixed output reference worked with a flexible rigid AFO [18,64] and an AFO with only mechanical actuators, such as an oil damper [69] and a spring [32,73]. The adaptive output reference could be observed from those works that utilized electrical actuators such as an MR device [41,49,56], SEA [54,75], and a pneumatic system [53].…”
Section: Output Reference: Fixed Versus Adaptivementioning
confidence: 99%
“…For the trial-and-error approach, the strut width is set beforehand in the module [19,59,64], as shown in Figure 6. The strut module, which is made of carbon fiber, connects the calf and foot parts by a screw mechanism that can be easily and quickly changed, when necessary [19].…”
Section: Bending Stiffness Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional data used in this study originate from the baseline visits of the PROOF-AFO trial (24). Data used are: orthotic properties, walking speed, walking energy cost, gait biomechanics and lower limb muscle strength.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…For this study, a convenience sample was used. The sample consisted of all participants of the PROOF-AFO trial (24). The sample size of the PROOF-AFO trial was calculated to demonstrate a 10% reduction in walking energy cost with a new stiffness-optimized AFO compared with a general prescribed AFO.…”
Section: Study Populationmentioning
confidence: 99%